Identification of rice mutant families with chilling tolerance - Getz, Barbara; Silva, Raíssa Martins da; Luz, Viviane Kopp da; Sousa, Rogerio Oliveira de; Magalhães Júnior, Ariano Martins de; Barbosa Neto, José Fernandes; da Maia, Luciano Carlos; Oliveira, Antonio Costa de (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to characterize chilling tolerance in rice mutant families of the M4 generation, at the seedling stage. Two experiments were carried out: chilling tolerance was evaluated in 43 mutant families, in the 'BRS Querência' original genotype, and in 19 commercial genotypes. In Experiment II, 8 mutant families from Experiment I, 'BRS Querência', and a mutant of the M5 generation were tested. In both experiments, seedlings were evaluated under two conditions: 10°C for seven days and 25°C for seven days. In Experiment I, the induced mutations in rice led to varied responses in chilling tolerance traits, with some M4 mutant families outperforming the original genotype. Experiment II highlighted the impact of mutations on chilling-tolerance, particularly in terms of leaf discoloration and plant recovery. Mutant families of the M4 generation differ from the original genotype 'BRS Querência' in chilling tolerance at the seedling stage. The mutant families M36, M54, and M56 and 'BRS Querência' show genetic similarity, indicating a lack of chilling tolerance during the seedling stage. The mutant families M17, M21, M22, and M26 are promising for rice breeding programs because they present chilling tolerance. The M30 mutant family exhibits the best performance for all analyzed traits, indicating chilling tolerance at the seedling stage.